Surgical options of the breast and clinical outcomes of breast cancer patients after neoadjuvant chemotherapy: A single-center retrospective study - Sang, Yuting; Zhou, Xujie; Chi, Weiru; Chen, Jiajian; Yang, Benlong; Hao, Shuang; Huang, Xiaoyan; Liu, Guangyu; Shao, Zhimin; Wu, Jiong (Frontiers in Oncology, 2022)
Background: Neoadjuvant chemotherapy (NAC) has evolved significantly and has been widely accepted for downstaging disease in early-stage and locally advanced breast cancer patients. Since the optimal surgical intervention for patients receiving NAC remains controversial, we aim to investigate the survival outcome of patients treated with different surgical management. Methods: A retrospective, nested case-control study was conducted in patients with invasive breast cancer that underwent NAC at Fudan University Shanghai Cancer Center from January 2010 to June 2019. Based on surgical intervention, patients were divided into mastectomy and breast conservation groups. Patients were matched on age at diagnosis, menopausal status, the year of the surgery, post neoadjuvant therapy pathological tumor (ypT) stage, post neoadjuvant therapy pathological node (ypN) stage, molecular subtypes, and axillary surgery by propensity score matching. Results: A total of 2080 patients were enrolled in this study. Among them, 1819 (87.5%) patients were categorized as mastectomy group, and 261 (12.5%) patients were classed as breast conservation group. Over 9-years of research, the proportion of breast conservation steadily increased in patients after NAC. Data showed that younger (P<0.001) and pre-menopausal (P<0.001) patients with normal BMI (P=0.022) were more likely to receive breast conservation. Patients at advanced ypT stage (P<0.001), ypN stage (P<0.001), and clinical TNM stage (P=0.002) were more often to undergo mastectomy, while breast conservation rate was significantly higher in patients with triple-negative tumors (P=0.023). Compared with the mastectomy group, significant benefits in overall survival were observed in patients who received breast conservation (Hazard ratio 0.41, [95% confidence interval: 0.18-0.97]; p=0.049) in the matched cohort. There was no statistical difference between groups related to disease-free survival and locoregional recurrence. Conclusions: Tumor biology can significantly impact the surgical decision in patients administrated with NAC. Breast conservation was a safe alternative for mastectomy in the NAC setting without compromising survival outcomes and locoregional control.